Lincoln's Inaugurals, Addresses and Letters (Selections) - Lincoln, Abraham, 1809-1865; Dodge, Daniel Kilham, 1863-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Lincoln's Inaugurals, Addresses and Letters (Selections)" by Abraham Lincoln is a collection of significant speeches and writings from one of America's most revered presidents, compiled in the early 20th century. This work encompasses Lincoln's reflections and speeches that were pivotal to American political and social discourse during the mid-19th century, particularly surrounding issues like slavery, civil rights, and national unity. It serves as a critical resource for understanding Lincoln$1 (Bs principles, values, and the historical context in which he led the nation through the Civil War. The opening of this collection offers a glimpse into Lincoln's early ambitions and insights, beginning with an address to the citizens of Sangamon County in 1832 as he announces his candidacy for the state legislature. In this speech, he discusses the importance of internal improvements, such as infrastructure and navigation, expressing his desire to serve the community$1 (Bs interests. He emphasizes the need for civic responsibility and intelligent discourse, setting a tone of earnestness and ambition that characterizes Lincoln's rhetoric throughout his career. The introduction highlights Lincoln's humble beginnings, intellectual growth, and moral convictions that shaped his leadership during a tumultuous period in American history. (This is an automatically generated summary.)s
Release date is 2004-12-06
Produced by Al Haines
Keywords: Lincoln, Abraham, 1809-1865; Presidents -- United States -- Inaugural addresses; Lincoln, Abraham, 1809-1865 -- Oratory; Lincoln, Abraham, 1809-1865 -- Correspondence